PERENCANAAN GEDUNG PERKANTORAN ARMADA II DI MAGELANG - Bakhtiar Ali Afandi; Mansyur Arifudin; Himawan Indarto; Ilham Nurhuda (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
The office building in this Final Project was designed to comply with Special Moment Resisting Frame System (SMRFS). The Special Moment Resisting Frame System (SMRFS) was chosen to enable the building to behave in ductile manner. This because ductile structures can disipate large amount of energy when subject to earthquake loading. The system was design to apply the concept of strong column weak beam, where the vertical elements of the structure (column) should be made stronger than the horizontal elements of the structure (beam), so that plastic joints occur on beam ends. Moreover, the beam-column joint connections were designed to avoid collapse in joints.